Nanomaterials targeting iron homeostasis: a promising strategy for cancer treatment - Li, Bin; Zhang, Bing; Cheng, Ziyue; Lou, Yantao; Chen, Shuqiu (Frontiers in Bioengineering and Biotechnology, 2025)
Iron is essential for vital cellular processes, including DNA synthesis, repair, and proliferation, necessitating enhanced iron uptake and intracellular accumulation. Tumor cells, in particular, exhibit a pronounced elevation in iron uptake to sustain their continuous proliferation, migration and invasion. This elevated iron acquisition is facilitated predominantly through the upregulation of transferrin receptors, which are closely associated with tumorigenesis and tumor progression. Incorporating transferrin into drug delivery systems has been shown to enhance cytotoxic effects in drug-sensitive cancer cells, offering a potential method to surpass the limitations of current cancer therapies. Intracellular iron predominantly exists as ferritin heavy chain (FTH), ferritin light chain (FTL), and labile iron pool (LIP). The innovation of nanocarriers incorporating iron chelating agents has attracted considerable interest. Iron chelators such as Deferoxamine (DFO), Deferasirox (DFX), and Dp44mT have demonstrated significant promise in cancer treatment by inducing iron deficiency within tumor cells. This review explores recent advancements in nanotechnology aimed at targeting iron metabolism in cancer cells and discusses their potential applications in cancer treatment strategies.